2018
DOI: 10.1002/qua.25869
|View full text |Cite
|
Sign up to set email alerts
|

Can halogen bond energy be reliably estimated from electron density properties at bond critical point? The case of the (A)nZ—Y•••X(X, Y = F, Cl, Br) interactions

Abstract: Relationships between the Y•••X bond critical point (BCP) properties or the Y•••X distance and the halogen bond interaction energy were analyzed in detail by theoretical methods for the series of structures [(A)nZ—Y•••X]− (X,Y = F, Cl, Br; totally 441 structures). No relationship was found for the whole set of structures or for the series [(A)nZ—F•••X]−, [(A)nZ—Cl•••X]−, and [(A)nZ—Br•••X]−. The interaction energies may be roughly estimated from the BCP properties for the series [(A)nZ—Y•••F]−, [(A)nZ—Y•••Cl]−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 196 publications
(40 reference statements)
2
38
1
Order By: Relevance
“…This finding has been discussed by us earlier for the halogen bonds formed by different atoms or fragments that play the role of halogen acceptors [45]. This fact has recently been illustrated in detail in Reference [46], where the large series of non-covalent interactions with different halide anions have been studied.…”
Section: Resultssupporting
confidence: 53%
“…This finding has been discussed by us earlier for the halogen bonds formed by different atoms or fragments that play the role of halogen acceptors [45]. This fact has recently been illustrated in detail in Reference [46], where the large series of non-covalent interactions with different halide anions have been studied.…”
Section: Resultssupporting
confidence: 53%
“…It was shown by Kozuch and Martin [95] for a set of 51 structures bearing XBs that the root-mean-square deviation, the mean signed error, and the maximum error of dissociation energy for M06-2X are 0.43, 0.01, and 1.58 kcal/mol, respectively, relative to the CCSD(T) method. Additionally, it was shown [92] that the E int (V b ) correlation for structures of the [(A) n Z–Y···F] − type (Y = F, Cl, Br) at the M06-2X level of theory has similar parameters as that for the MP4, CCSD, and CCSD(T) methods (see Figure 7A in [90]).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Since the publication of the EML formula, numerous but usually not justified attempts to apply this relationship to different types of non-covalent interactions were undertaken. However, it was shown that these equations may not be universal, and their validity may be restricted only to the type of interactions for which they were deduced [91,92]. Thus, there is a great practical need to establish the reliable E int (property) relationships for the most important types of non-covalent interactions others than the X–H···O, FH···FR, and Y–Hal···Z(B) m ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Reference [41] EML formula in most cases underestimated the energy of intermolecular interactions by substantial amount as compared to the method implemented to CrystalExplorer program (CE-B3LYP). Severe judgement about EML correlation were expressed in the paper by Kuznetsov [42]. On the other hand, according to other published articles the lattice energies calculated from EML correlation provided reasonable values that agreed with experimental sublimation heat [43][44][45].…”
Section: Lattice Energies and The Role Of F F Interactionsmentioning
confidence: 78%